Open- and Closed-Skill Exercise Interventions Produce Different Neurocognitive Effects on Executive Functions in the Elderly: A 6-Month Randomized, Controlled Trial - Tsai, Chia-Liang; Pan, Chien-Yu; Chen, Fu-Chen; Tseng, Yu-Ting (Frontiers in Aging Neuroscience, 2017)
This study aimed to explore the effects of open- and closed-skill exercise interventions on the neurocognitive performance of executive functions in the elderly. Sixty-four healthy elderly males were randomly assigned to either a closed-skill (bike riding or brisk walking/jogging, n=22), open-skill (table tennis, n=21), or control (n=21) group. Various neuropsychological [e.g., accuracy rates (AR) and reaction time (RT)] and electrophysiological [e.g., event-related potential (ERP) P3 component] measures were assessed during a variant of the task-switching paradigm, as well as an N-back task at baseline and after either a 6-month exercise intervention or control period. The results showed that, when performing the task-switching paradigm, the two exercise groups relative to control group showed significantly faster RTs in the switch trials after the exercise intervention. However, the RT facilitation in the non-switch and switch trials post-exercise relative to pre-exercise only emerged in the open-skill group. In terms of the N-back task, the two exercise groups significantly increased ARs in the 1-back condition after the exercise intervention, and the beneficial AR effect on the 2-back condition only emerged in the closed-skill group. In addition, the two exercise groups exhibited significantly larger P3 amplitudes on the frontal-to-parietal cortex areas after the exercise intervention relative to the baseline when performing the two cognitive tasks. These neurocognitive results still remained unchanged even when the confounding factors (e.g., cardiorespiratory fitness, social participation, and BMI) were controlled for. The present study concluded that, although 6-month open- and closed-skill exercise intervention facilitates overall electrophysiological effects (i.e., increased ERP P3 amplitudes) on the frontal-to-parietal cortices in the elderly, the two exercise modes produced different levels of neuropsychologically beneficial effects on RTs of the task-switching paradigm (i.e., lessened RTs) and ARs of the N-back task (i.e., enhanced ARs). The distinctive neurocognitive changes induced by open- and closed-skill exercise have implications for task switching and working memory in elderly individuals, especially with such cognitive functioning impairments.